FRI0044 IL-1 dependent SYNDECAN-4 signal transduction is mediated by its heparan sulfate side chains in RA synovial fibroblasts. (23rd January 2014) - Godmann, L.; Stratis, A.; Cromme, C.; Frank Echtermeyer, E.; Pap, T.; Bertrand, J.
Abstract : Background: In rheumatoid arthritis (RA) pathogenesis, activated synovial fibroblasts (SFs) play an important role, because of their tumor-like and agressive behavior. This phenotype is promoted by a steady stimulation with growth-factors and inflammatory cytokines, such as IL-1. Syndecan-4 (sdc4), a transmembrane heparan sulfate proteoglycan, has been found to be upregulated in RA-SF. Sdc4 can act as membrane receptor for a large array of ligands and modulate cytokine signaling by binding of molecules, such as TGFbeta, to its side chains. Very recently, sdc4 was discovered to modulate Erk signaling in chondroytes in response to IL-1 stimulation. Objectives: Since the exact mechanisms of sdc4 signaling according to the role of sdc4 side chains are still unknown, we investigated sdc4 signal transduction with sdc4 side chain mutants as well as knock-out fibroblasts. Methods: In order to unravel the role of sdc4 side chains for sdc4 signal transduction, we designed different sdc4 side chain mutants via overlap PCR. The serine residues, which constitute the side chain attachment sides, where replaced by alanine residues, thereby abolishing side chain formation. To analyze membrane localization of the designed mutants, laser scanning fluorescence microscopy of transiently transfected Cos-7 cells was performed. To investigate the multimerization pattern of the different sdc4 mutants crosslinking was performed upon IL-1 stimulation and subsequent Western blot analysis. Moreover, fibroblasts lacking sdc4, the IL-1 receptor (IL1-RI) or both receptors were stimulated with IL-1 to elucidate the interaction between IL-1RI and scd4 in IL-1 signaling. The phosphorylation pattern of Erk1/2 was chosen as readout. Results: Every sdc4 side chain lacking mutant revealed normal intracellular trafficking into the cell membrane. Although wild type sdc4 showed normal multimerization, an impaired complex formation could be observed for the side chain mutants, particularly with regard to tetramers. Additionally, our crosslinking experiments displayed that sdc4 undergoes dimerization due to IL-1 stimulation. Analyzing sdc4 signal transduction in sdc4 -/- fibroblasts revealed a diminished IL-1 induced Erk1/2 phosphorylation, while IL-1 induced Erk1/2 phosphorylation was nearly completely abolished in cells lacking the IL-1RI. Fibroblasts lacking both, IL-1RI and sdc-4, did not respond to IL-1 stimulation with an increased Erk1/2 phosphorylation. Comparing the impact of IL-1α and IL-1β on Erk1/2 phosphorylation, IL-1β was found to lead to a faster and more pronounced elevation of Erk1/2 phosphorylation in comparison to IL-1α. Conclusions: In conclusion, we have shown that heparan sulfate side chains are essential for sdc4 multimerization and IL-1 stimulation induces sdc4 dimerization. Furthermore, sdc4 plays a role during IL-1 signaling and can be assumed to play an additive or even regulatory role in IL-1 signaling. Consequently, sdc4 complex formation might be a keystone in signal transduction during RA disease progression in RA-SF. Disclosure of Interest: None Declared